Moderate beer consumption and metabolic health: A comprehensive review from the lipoprotein perspective. (August 2022) - Grao-Cruces, Elena M.; Montserrat-de la Paz, Sergio; Martin, Maria E.
Graphical abstract: Highlights: Moderate beer consumption modulates cardiovascular health parameters. Moderate beer consumption modulates the blood lipid profile. Beer components and matrix are essential for its properties. It is not clear whether alcohol or phenols are the main responsible of beer effects. Abstract: Beer intake is part of our society lifestyle but still a controversial topic due to the lack of consensus regarding its effects on our health. Regarding cardiovascular disease, research needs to consider the amount consumed but also drinking thresholds, frequency of drinking, age and gender of consumers, lifestyle, or non-alcoholic components of beers. Nevertheless, epidemiological evidence points to healthy effects of low or moderate beer consumption and even a protective action for cardiovascular risk and diabetes, discouraging heavy intakes without any exception. Beer components include alcohol and phenolics, both of which alter high- or low-density-lipoprotein levels and their oxidation status in blood. This review aims to highlight the importance of the metabolic mechanism by which beer components may influence lipid profile in terms of quantity and functionality, modulating cardiovascular risk. This is a major challenge for our society in light of the remarkable impact of cardiovascular diseases in all-cause mortality.